2008
DOI: 10.1016/j.molimm.2007.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Ets factors and a newly identified polymorphism regulate Fli1 promoter activity in lymphocytes

Abstract: Fli1 is an Ets family member that is essential for embryonic development. Increasing evidence suggests modulating Fli1 gene expression impacts lymphocyte development/function and is an important mediator in the autoimmune disease lupus. Fli1 is over-expressed in splenic lymphocytes in lupus prone mouse strains and in PBMCs of lupus patients. Presently, it is unknown how Fli1 gene expression is controlled in lymphocytes or how it becomes over-expressed in lupus. Therefore, we examined Fli1 regulation in a murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 38 publications
8
32
1
Order By: Relevance
“…These data suggest that the absence of the CTA domain of Fli1 may interfere with the autoregulation at the transcriptional level, consistent with recent studies that demonstrated involvement of Fli1 in regulating its own expression in lymphocytes (25). We next quantified procollagen type I, III, and V mRNAs using quantitative PCR in the skin tissues of WT and Fli1…”
Section: Resultssupporting
confidence: 87%
“…These data suggest that the absence of the CTA domain of Fli1 may interfere with the autoregulation at the transcriptional level, consistent with recent studies that demonstrated involvement of Fli1 in regulating its own expression in lymphocytes (25). We next quantified procollagen type I, III, and V mRNAs using quantitative PCR in the skin tissues of WT and Fli1…”
Section: Resultssupporting
confidence: 87%
“…The GA n repeat element in exon 1 is located directly adjacent to Fli1 regulatory elements, specifically, a GATA/EBS dual element known to act as a transcriptional enhancer (5,6,25,26). The GA n repeat element is a known endogenous enhancer of Fli1, and the length of this repeat is inversely correlated with Fli1 promoter activity, i.e., the longer the repeat, the lower the promoter activity and gene expression (25). In B6 mice, the length of the GA n element is 28 GA repeats, and in Bc mice, it is 29 GA repeats.…”
Section: Discussionmentioning
confidence: 99%
“…Any of the three polymorphisms identified may be the cause of the differential disease and gene expression profiles observed between mice carrying the B6 or Bc Fli1 allele; however, of the three polymorphisms observed, the GA n repeat element is of the most interest. Unlike the GT n repeat element and TT deletion event, the GA n repeat element is 100% conserved between mice and humans and is a known endogenous enhancer of Fli1 expression; the length of this repeat is inversely correlated with Fli1 promoter activity (25).…”
Section: Vol 78 2010 Fine Mapping Of Leishmania Major Response Locumentioning
confidence: 99%
“…Each real-time reaction was performed in triplicate on the MyiQ Bio-Rad Thermocycler using the iQ SYBR Green Supermix (Bio-Rad), and threshold cycle number for each reaction was determined using the Real-Time iCycler iQ software (Bio-Rad). Relative expression was calculated using the Bio-Rad Gene Expression Macro software as described previously 39 with b-actin as the reference gene. Relative differences between groups are presented as fold change.…”
Section: Gene Expressionmentioning
confidence: 99%